Study the anti – inflammatory effect of Stevia rebaudiana sweetness in vitro - Meison Abdulbary; Albasheer Ammar; Muhanad Mohammed; Wafaa Yousif; Suaad Lateef Ibrahim (Al-Qadisiyah Journal of Pure Science, 2021)
Because of the high rates of diabetes, overweight disorders and fatness, the need and interest in finding alternatives to sugar has increased, especially in the industrial sector in parallel with reducing the daily intake of sugar by human. The idea of this research was developed to identify the active ingredients which include in the plant aqueous extract of Stevia rebaudiana. Chemical examination showed the glycosides and phenolic compounds presence of in the Stevia rebaudiana plant. The effect of Stevia rebaudiana leaves products aqueous extract as anti-inflammation measured in vitro with two procedures , The repression of protein denaturation and hemolysis stimulated by heating and results showed Stevia rebaudiana efficiency with compared to typical medicine (Aspirin) and negative control groups.